A Faunal Interpretation of Tidal Evolution in Minas Basin, Nova Scotia - Wagner, Frances (Géographie physique et Quaternaire, 1980)
Interpretation of the evolution of the tidal cycle in Minas Basin and upper Bay of Fundy (Scots Bay) based on molluscan assemblages agrees well with that derived by AMOS (1978) from sedimentological evidence. Prior to about 6300 years B.P. quiet water conditions, i.e. with minimal or no tidal activity, prevailed. From that time, tidal range and intensity have increased to their present levels. The molluscs show this change by a change from intact specimens of deposit feeders at, or near, the base of two of the vibrocores, through a mixture of incomplete specimens and suspension feeders, to accumulations of minute, unidentifiable shell fragments.